Effects of Drainage Technology on Waterlogging Reduction and Rice Yield in Mid-Lower Reaches of Yangtze River - Bowei Qi; Shenjiao Yang; Dongwei Li; Dandan Qin; Xingfei Zheng; Jianlin Hu; Xinguo Zhou; Hongquan Liu (Agronomy)
As extreme rainfall events become more frequent, leading to increased waterlogging hazards, it is crucial to explore various drainage methods that can alleviate the adverse effects of waterlogging on crop growth, thus addressing challenges related to global food security. Field experiments were carried out to evaluate the impacts of different drainage technologies on waterlogging mitigation, rice growth, dry matter accumulation, and yield. The experimental setup included varying straw blind ditch spacings (2, 3, 4, and 5 m) and subsurface pipe drainage spacings (6, 9, and 12 m), with surface drainage serving as the control (CK). The findings revealed that, in comparison to pipe drainage treatments, blind ditch treatments enhanced subsurface drainage volume by 15.1%. Regarding groundwater levels and soil moisture, the soil moisture in the 0–90 cm soil layer and groundwater levels under the blind ditch treatments were 11.3% and 6.1% lower than those under the CK as well as 22.0% and 23.9% lower than the pipe drainage treatments, respectively. Subsurface drainage treatments led to significant improvements in rice yield, with blind ditch and pipe drainage treatments increasing the yield by 8.0% and 6.0% compared to the CK. Rice yields initially increased before decreasing as burial spacing reduced. The S3 treatment resulted in yield increases of 14.4%, 8.6%, and 10.7% over the S2, S4, and S5 treatments, respectively. The G9 treatment produced 3.6% and 10.4% higher yields compared to the G6 and G12 treatments. The highest rice yield, 7.501 Mg·ha−1, was achieved with a blind ditch spacing of 3 m. Compared to the S4 and S5 treatments, the yield per hectare for the S3 treatment was higher by 0.592 Mg and 0.726 Mg, while the input cost was higher by CNY 3038 and 4560, respectively. Path analysis indicated that root biomass made the largest direct contribution (0.517) to the increase in rice yield. Subsurface drainage contributed to the regulation of soil moisture, reducing leaf biomass while increasing stem biomass, which enabled the blind ditch treatments to produce optimal rice yield. These results provide a scientific basis for agricultural drainage in waterlogged areas.